2003
DOI: 10.1023/b:appl.0000004931.07292.55
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a Bluff-Body Stabilised Nonpremixed Flame with Differential Reynolds-Stress Models

Abstract: Abstract.A numerical investigation of a bluff-body stabilised nonpremixed flame, and the corresponding nonreacting flow, has been performed with differential Reynolds-stress models (DRSMs). The equilibrium chemistry model is employed and an assumed-shape beta function PDF approach is used to represent the interaction between turbulence and chemistry. The Reynolds flux of the mixture fraction is obtained from a transport equation, hence a full second moment closure is used. To clarify the applicability of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 22 publications
4
27
0
Order By: Relevance
“…Turbulence is modeled using the second-moment closure RANS model of [20]. This is the isotropization of production model of [27], with modified constant value C ε1 = 1.6, instead of the standard value C ε1 = 1.44.…”
Section: Turbulence Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulence is modeled using the second-moment closure RANS model of [20]. This is the isotropization of production model of [27], with modified constant value C ε1 = 1.6, instead of the standard value C ε1 = 1.44.…”
Section: Turbulence Modelmentioning
confidence: 99%
“…In order to achieve good agreement to experimental data for the turbulent flow field, in terms of radial profiles in physical space of mean velocities and velocity fluctuations, a second moment closure model is applied with modified model constants [4,20]. Good quality of the results is obtained up to the neck zone.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the prediction of temperature profiles at downstream locations were not good. Li et al [16] investigated this flame using various differential Reynolds stress models with the equilibrium chemistry model. They reported that all the differential stress models in the standard form failed to reproduce the mean velocity, velocity fluctuations, mean mixture fraction and its variances.…”
Section: Introductionmentioning
confidence: 99%
“…From the comparative study presented in [29] for the bluff-body flame HM1, the LRR-IPM Reynolds-stress model is used with the modified constant value C 1 = 1.6. Figure 1 shows that the mean flow field is reasonably well predicted as in [29,10].…”
Section: Flow Fieldsmentioning
confidence: 99%